Synthetic MRI for Radiotherapy Planning for Brain and Prostate Cancers: Phantom Validation and Patient Evaluation - Gouel, Pierrick; Hapdey, Sebastien; Dumouchel, Arthur; Gardin, Isabelle; Torfeh, Eva; Hinault, Pauline; Vera, Pierre; Thureau, Sebastien; Gensanne, David (Frontiers in Oncology, 2022)
Purpose: To evaluate the accuracy of T1 and T2 mappings derived from a multispectral pulse sequence (MAGiC®) on 1.5 T MRI, and with conventional sequences (GRE-VFA and ME-SE) compared to reference values for radiotherapy treatment planning purpose. Methods: The accuracy of T1 and T2 measurements was evaluated with 2 coils (HNU and BODY) on phantoms, using descriptive statistics and Bland-Altman analysis. Reproducibility and repeatability of T1 and T2 measurements were performed on 15 sessions with the HNU coil. The T1 and T2 synthetic sequences obtained by both methods were evaluated according to quality assurance requirements (QA) for radiotherapy. In vivo measurements of T1 and T2 of the brain or prostate tissues of two groups of five subjects were also compared. Results: The phantom results show good agreement (mean bias 8.4 %) between the two measurement methods for T1 values between 490 and 2385 ms and T2 values between 25 and 400 ms. MAGiC® gives discordant values for T1 values below 220 ms (bias with the reference values from 38 % to 1620 %). T2 measurements are accuracy estimated bellow 400 ms (mean bias 8.5 %) for both methods. The QA are in agreement with the recommendations of imaging for contouring purposes for radiotherapy planning. On patient data of the the brain and prostate, the measurements of T1 and T2 by the two qMRI methods were comparable (max difference <7 %). Conclusion: This study shows that the accuracy, reproducibility and repeatability of the multispectral pulse sequence (MAGiC®) were compatible with its use for radiotherapy treatment planning, in a range of values corresponding to soft tissues. Even validated for brain imaging, MAGiC® could potentially be used for prostate qMRI.